It's a stick-up - Ollystudio (Laurence King Pub., 2013)
This is the first book to look at an increasingly popular form of street art: the paste-up or ""wheatie."" Many street artists don't graffiti or stencil any more but use pre-prepared paper images that can be taken down, thereby avoiding a vandalism charge. The book shows the work of 20 artists, with photographs of their work, an article about their work, and a fold-out paste-up. The fold-out pages are perforated so they can easily be removed. Some of the paste-ups are laser cut with attaching tags so they can be popped out. There's also an introductory interview with cult street artists Sten &